2021
DOI: 10.17860/mersinefd.781097
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Attitudes towards Distance Education and Readiness for E-Learning of Education Faculty Students

Abstract: Öz: Yeni Koronavirüs (Covid-19) olarak adlandırılan virüs salgını nedeniyle birçok ülkede olduğu gibi Türkiye'de de eğitimler uzaktan eğitimle yürütülmeye başlandı. Bu araştırmada, örgün öğrenime kayıtlı olduğu halde bu salgın döneminde uzaktan eğitim alma durumunda kalan eğitim fakültesi öğrencilerinin uzaktan eğitime karşı tutumları ve e-öğrenmeye hazır bulunuşlukları çeşitli değişkenler bağlamında incelenmiştir. Betimsel tarama niteliğindeki araştırmanın katılımcılarını Kahramanmaraş Sütçü İmam Üniversitesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
1
10
0
7
Order By: Relevance
“…Similar to our results, Sarıtaş and Barutçu (2020) determined that undergraduate students' self-directed learning status and motivation were high, but their learning control was the lowest (37). In studies examining readiness for e-learning, Yakar and Yakar (2021) and Coşkun et al (2018) found that students' motivation levels for e-learning were low (20,26). In studies examining students' online learning controls, there are studies reporting low learning control (23,32,37) and also high learning control (34).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to our results, Sarıtaş and Barutçu (2020) determined that undergraduate students' self-directed learning status and motivation were high, but their learning control was the lowest (37). In studies examining readiness for e-learning, Yakar and Yakar (2021) and Coşkun et al (2018) found that students' motivation levels for e-learning were low (20,26). In studies examining students' online learning controls, there are studies reporting low learning control (23,32,37) and also high learning control (34).…”
Section: Discussionsupporting
confidence: 86%
“…Students must to be ready and have a positive attitude in order to benefit from online learning processes efficiently (26). According to findings of the study, as the readiness levels of nursing students towards online learning improved, so did their attitudes towards web-based learning and their positive attitudes about web-based learning succesfully increased.…”
Section: Discussionmentioning
confidence: 91%
“…Erdoğan (2022) stated that the structure of education shapes the professional development processes, and that the decisions and contents of educational activities in Turkey are determined by the Ministry of National Education. When the studies emphasizing the environmental context are examined, it is seen that the school readiness level of the children in the upper socio-economic group is higher than the children in the lower socioeconomic group (Erkan, 2011), and at the same time, the parents attend the meetings less in the environment with the lower socioeconomic level (Bellibaş, 2003). Maxwell (2016), Uline and Tschonnen Moren (2008), Şensoy and Sağöz (2015) found in their studies that the physical infrastructure of the school mediates student success.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In terms of its structure and function, education is one of the fields that has been affected by social issues mostly. On account of virus outbreak that emerged in China in 2019 and called the new type of coronavirus (COVID-19), interruption of face-to-face education and the transition to distance education in many countries can be shown as the latest example of this situation (Yakar & Yıldırım-Yakar, 2021). Owing to this coronavirus outbreak that gave rise to a global crisis, teaching activities in Turkey in the 2019-2020 academic year started to be carried out via distance education (YÖKAK, 2020a).…”
Section: Introductionmentioning
confidence: 99%